Характеристика контенту професійних видань - Голік, Оксана В.; Golik, O. V. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті характеризується контент професійних видань, що визначається їх функціональним призначенням та читацькою аудиторією. Визначається, що особливістю професійних (фахових) видань є сталість рубрик, послідовність та певна прогнозованість змістового наповнення, що пояснює офіційність стилю викладу матеріалу, принципи оформлення та певна обмеженість жанрової палітри. In the article the content of professional editions, that is determined by their functional setting and reader audience, is characterized. In the printed press the professional editions are occupied their place, that yet name branch, thematic, specialized. Their main feature consists in the having (functional) a special purpose setting, that determines essence of edition, its orientation, reader audience, article of exposition, content, journalistic genres, design, system of rubrication. It is determined that the features of professional editions are constancy of heading, sequence and certain forecast of the semantic filling, that explains officialness of style of exposition of material, principles of design and certain limit of genres.
Description of Content of Professional Editions
Keywords: контент; content; рубрика; heading; професійне видання; professional edition; функціональне призначення; functional setting; автор; author